Implementation of Pancasila Values in The Era of Globalization - Hayat, Nahrul; Bagus Siddiq, Muhammad (International Journal of Students Education, 2023)
This study aims to deepen our awareness of the application of Pancasila ideals in the context of globalization, which some people may have forgotten because of the pressures that come with it. Problems as a result. This research uses a descriptive approach in a qualitative way. The research shows that Indonesian culture. The findings of this study show that, even in the current era of globalization, there are still many Indonesians who do not live according to the norms of Pancasila in their daily associations and relationships. There are even those who have lost sight of the principles of Pancasila and the guidelines for Indonesian life. The ideals of Pancasila are still widely ignored in daily life and some people in the contemporary globalization era even ignore the ideas contained in Pancasila as a way of viewing Indonesian society and daily life. The values contained in Pancasila are an inseparable part of it. Therefore, if the ideals of Pancasila are combined with a moral foundation and utilized in interstate relations, they have the potential to become a powerful moral force. Pancasila is a value system that exists as an unbreakable unity. As a result, Pancasila values, if used as a moral foundation in the life of the nation and state, have the potential to become a powerful moral force. In the era of globalization, teaching Pancasila ideals to children can be done at the right time. For example, on Youth Pledge Day, Independence Day, Heroes’ Day, and other national holidays, students can strive for the best achievements and be serious in studying. I really enjoy and love using domestic products for the benefit of the nation’s economic progress, using all my abilities to uphold the honor of the state and nation.